2019
DOI: 10.2147/jmdh.s214120
|View full text |Cite
|
Sign up to set email alerts
|

<p>Immersive placement experiences promote rural intent in allied health students of urban and rural origin</p>

Abstract: IntroductionPre-vocational placement experiences are known to considerably influence the career preferences of health graduates and are a key factor in growing the rural allied health workforce. This paper explores the rural placement experiences and future work intentions of students who attended a placement with the University of Newcastle Department of Rural Health.MethodsPart of a larger longitudinal mixed methods study of students’ placement experiences and subsequent career choices, this study explored s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(57 citation statements)
references
References 28 publications
(41 reference statements)
4
47
0
Order By: Relevance
“…Finally, the insufficiencies of the patient-clinician relationship are brought into question. Patient counselling remains a critical element in reducing LTFU [38] reducing LTFU pointing to integrated behavioural counselling and TB care promoting adherence to treatment protocols [41,42]. Clinicians require knowledge of TB disease and its management and excellent communications skills to ensure quality patient education and communication [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the insufficiencies of the patient-clinician relationship are brought into question. Patient counselling remains a critical element in reducing LTFU [38] reducing LTFU pointing to integrated behavioural counselling and TB care promoting adherence to treatment protocols [41,42]. Clinicians require knowledge of TB disease and its management and excellent communications skills to ensure quality patient education and communication [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence shows that rural background is apparently the most strongly influential factor on graduates' choice of rural practice location 10‐12,21‐23 . However, rural practice intentions at commencement of studies 14‐16,20,21 and exposure to rural health care settings during their education and training 8,10,14,23,24,29 are also key indicators of postgraduate rural practice. Indeed, some studies have suggested that rural placement experience might be a stronger predictor of rural practice intentions than rural background 19,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐seven articles (53%) focused on education strategies: student placements and internships ( n = 16), decentralised education ( n = 7), and creating a rural pipeline ( n = 4) (, Table 4.2) 14-40 . Studies examining different modes of undergraduate program delivery were conducted in most countries.…”
Section: Resultsmentioning
confidence: 99%